Programa de orientación vocacional laboral para personas con discapacidad de la fundación de adaptación laboral-IDEAL. - Arango-Soler, Juan M.; Santander, Johann M.; Correa-Moreno, Yerson A. (Revista de Salud Pública)
Objective Optimizing the IDEAL foundation's vocational guidance program for its disabled beneficiaries to promote their satisfactory performance in the institutional workshop and in their daily lives, aimed at their future re insertion into the labor market. Methods This was a cross-sectional descriptive study involving 20 handicapped people from the IDEAL foundation's vocational guidance program who had been assigned a workshop activity. This sample was characterized by using a battery of tests based on IDEAL's institutional format called Abilities and Skills. Workplace in IDEAL's workshop and occupational evaluation of the workers was analyzed using the integral occupational evaluation methodology (MIEO) categories proposed by the Latin-American Professional Rehabilitation Group (GLARP) as part of their Handicapped Disabled People's Standardized Integration Project. Users' individual abilities were compared to the requirements of their workplaces, based on the institutional format's categories. Results The evaluation methodology based on the institutional Abilities and Skills format had limitations, thereby hampering its implementation. Most users performed well regarding their assigned work shop activities, responding well to sensory-perception, motor function and mental processing requirements; however, they engaged in poor healthcare habits. Discussion Diversification of the activities to which the users/beneficiaries have access should be encouraged, promoting individual performance by providing options offering a wider scope than just that of the labor market/workplace. Production-related considerations have led the workshop's users to adopt practices endangering their health and putting their welfare at risk.